Varietal Evaluation of French bean for Higher Productivity and Nutritional Security under the Foot Hill Ecosystem of Nagaland - Zeliang, Patu K; Kumar, Manoj; Kumar, Rakesh; Meena, K.L.; Rajkowa, D.J. (Indian Journal of Hill Farming, 2019)
On farm trial was conducted at farmers’ field by Krishi Vigyan Kendra, Longleng, Nagaland for evaluation of high yielding French bean varieties for optimization of crop productivity and nutritional security of poor tribal community. Results revealed that yield attributes i.e. pod weight; pod length and pods/plant were markedly influenced by frenchbean cultivars among themselves. The highest pod weight (11.3g), pod length (11.3 cm) and pods/plant (24.1) were recorded with Arka Anoop, which were significantly higher as compared to Arka Komal and Arka Suvidha. However, the lowest values of these attributes were associated with local cultivar. Similarly, significantly higher green pod yield was recorded with Arka Anoop (6.5 t/ha) followed by Arka Komal (6.1 t/ha) and Arka Suvidha (5.8 t/ha). Hence, it may be concluded that Arka Anoop may be adopted for commercial cultivation for achieving higher productivity and profitability under foot hill ecosystem of Nagaland.